Retreatment of symptomatic hepatitis C virus genotype 3 associated mixed cryoglobulinemia with sofosbuvir and ribavirin: a case report - Zarębska-Michaluk, Dorota (Clin Exp Hepatol, 2018)
A 52-year-old woman with chronic hepatitis C virus genotype 3 infection developed clinically symptomatic mixed cryoglobulinemia. She started pegylated interferon and ribavirin therapy and in week 12 became negative for HCV RNA with resolution of clinical signs of cryoglobulinemia. The dual treatment was discontinued due to interferon-related bilateral retinopathy. After therapy cessation, relapse of HCV RNA and recurrence of symptomatic cryoglobulinemia were observed. While waiting for the antiviral retreatment option she developed glomerulonephritis with renal impairment. Successful HCV eradication was achieved with 24-week treatment of sofosbuvir and ribavirin despite this regimen being considered as suboptimal therapy for genotype 3 HCV infection. A sustained virological response resulted in lasting resolution of clinical symptoms of mixed cryoglobulinemia.